Non Performing Loan Resolution Strategies and Impact on Financial Performance - Baharuddin, Ceskakusumadewi; Liutfi, Anugrah; Ar, Dhita Pratiwi; Rizal, Muhammad; Sasmita, Halida (Golden Ratio of Mapping Idea and Literature Format, 2025)
This study investigates the relationship between non-performing loan (NPL) resolution strategies and financial performance among commercial banks in Indonesia. As NPLs remain a persistent threat to banking sector stability, especially in post-pandemic recovery phases, the research aims to assess how various resolution mechanisms namely restructuring, write-offs, asset sales to asset management companies (AMCs), and digital early-warning systems impact key financial indicators such as return on assets (ROA), return on equity (ROE), net interest margin (NIM), and capital adequacy ratio (CAR). Employing a quantitative descriptive design, this study draws on secondary panel data from 35 Indonesian commercial banks over the 2020–2024 period, incorporating bank-level financial reports, regulatory disclosures, and macroeconomic indicators. Multiple regression analysis is used to evaluate the effect of each resolution strategy on financial performance metrics. The findings indicate that proactive loan restructuring has a significant positive effect on ROA and NIM, while asset sales to external AMCs are associated with notable improvements in CAR due to risk-weight reductions. Moreover, banks with aggressive provisioning policies experience enhanced ROE when combined with effective loss recognition. The implementation of AI-based early-warning systems significantly mediates the impact of restructuring on profitability by reducing re-default rates. These results suggest that an integrated resolution approach combining traditional financial tactics with digital risk-management innovations optimizes both short-term profitability and long-term solvency. The study contributes to strategic financial management literature and provides actionable insights for regulators aiming to strengthen bank resilience in emerging markets.